MODERN APPROACHES TO ANTICOAGULANT THERAPY DURING CATHETER ABLATION TREATMENT OF NON-VALVULAR ATRIAL FIBRILLATION - E. A. Belikov; K. V. Davtyan; O. N. Tkacheva (Рациональная фармакотерапия в кардиологии, 2015)
Prevention of thromboembolic complications in patients with atrial fibrillation during catheter pulmonary veins isolation is discussed. This subject review is presented with special consideration to new anticoagulants.